ANALISIS FRAGMENTASI GC-MS SENYAWA AKTIF ANTIKANKER LEUKEMIA FRAKSI KLOROFORM UMBI BAWANG TIWAI (Eleutherine bulbosa (Mill.) Urb) - Dwi Lestari; Rudi Kartika; Eva Marlina; Eka Siswanto Syamsul (Jurnal Ilmiah Manuntung, 2019)
Tiwai Onion (Eleutherine bulbosa (Mill.) Urb.) is an Iridaceae tribe which is a typical plant of Borneo. Its used by the Dayak community, among others, for colon cancer, breast cancer, diabetes mellitus, hypertension, lowering cholesterol, strokes, boils, anti-bleeding and abdominal pain. The purpose of this study was to determine the components of anticancer compounds of chloroform fraction by GC-MS method. The results of GC-MS spectrum analysis based on the base peak equation of the chloroform fraction contain 9,12-Octadecadienoic Acid, and 1- (2,3,5,6-Tetramethyl phenyl) Ethanone which has the potential as an anticancer.